Greenland, Boyd's Ship, Veslekari at Muskox Fjord, Hudsons Land - Boyd, Louise Arner, 1887-1972 (1931)
Inner end. Photo taken on north side of this fjord showing S. S. Veslekari anchored where anchor mark is on Nathorst Map. On left is seen delta and its many water-ways The delta makes the fjord so shallow it was impossible to take the S. S. Veslekari further in the fjord. L. A. B., accompanied by Mr. and Mrs. Menzies and de Gisbert (by motor launch), succeeded in reaching the extreme inner end and making a landing there on south side. Photo looking S. E. July 22, 1931 Muskox Fjord, Hudsons land of East Greenland